A DFT Study on Adsorption Behavior of CO on Pristine and Doped \(B_{12}P_{12}\) Nanocage - Hojatkashani, Leila (Challenges and Advances in Chemical Science Vol. 2, 2021)
Adsorption of the pollutant gas CO on B12P12 nanocage surface is studied through density functional calculations. HOMO and LUMO energy levels, binding energies and energy bond gaps of three possible configurations of CO on pristine B12P12 has been calculated by means of B3LYP and M062X functional with 6-31g+ basis set. The results showed that there is none or very slight adsorption of CO molecule by pristine B12P12.To overcome the fault, CO adsorption is investigated on Al and N doped B12P12 nanocage with the same method and basis set. The electronic and structural parameters like HOMO and LUMO energy levels and binding energies of possible configurations are calculated and showed that doped B12P12 with both Al and N atoms have increased about % 1.7 with CO molecule which also indicates more Vander Waals attraction between CO and Al and N doped B12P12 nanocage.